APPLICATION OF COLLECTIVE LEARNING TECHNOLOGY BASED ON THE DESKTOP AS A SERVICE CLOUD COMPUTING MODEL - Tileubai, С.Ш.; Doszhanov, Б.А.; Sabitbek, А.С. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
Currently, one of the main trends in the development of education today is the introduction of new information and cloud technologies in the educational process. Cloud technologies as an auxiliary technical tool for the organization of education allow to ensure a high level of access to education, improve the quality of education. Cloud technologies in education are based on the formation of learning collaboration between students through the remote organization of collective learning technologies, and for this purpose, the Desktop as a service cloud computing model optimizes the educational process by providing teachers and students with fully managed virtual desktops. The article highlights the importance of collective learning technologies, provides Desktop as a service solution for collective interaction with cloud systems, and studies the experience of foreign universities in applying the Desktop as a service cloud computing model.